ENHANCING ENGLISH PROFICIENCY THROUGH A TOEFL WORKSHOP AT MAN 1 GRESIK: PENINGKATAN KEMAHIRAN BAHASA INGGRIS MELALUI PELATIHAN TOEFL DI MAN 1 GRESIK - Indasari, Nur Laili; Rosyidi, Ali; Achadiyah, Rachmawati (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: In academic contexts, the Test of English as a Foreign Language (TOEFL) is one of the key requirements for career advancement, further study, scholarship opportunities, and entering the workforce. For senior high school students, the TOEFL poses a significant challenge when pursuing higher education or scholarship opportunities at domestic and international universities. Objective: This activity aimed to provide insights into the importance of the TOEFL, offer practical tips and strategies for taking the test, and facilitate a TOEFL prediction test. Method: A total of eighty students from MAN 1 Gresik participated in the TOEFL workshop, which consisted of three stages: planning, implementation, and evaluation. The evaluation was conducted through student interviews, incorporating three Likert-scale questions and two open-ended questions to assess the effectiveness of the workshop and participants’ satisfaction. Results: The results of the workshop indicated that students need to practice TOEFL tasks intensively to achieve optimal scores. The challenges faced by participants drew the attention of both the school and the community service team to improve support, particularly in addressing technical difficulties encountered during online test practice. Conclusion: This community service initiative contributes to the school’s efforts to enhance students’ English proficiency, particularly in assisting twelfth-grade students in preparing for admission to their desired universities.